Grid nano-indentation as full-field measurements. (May 2020) - Gaillard, Y.; Amiot, F.
Abstract: The use of grid nano-indentation as a full-field measurement tool to investigate the properties of heterogeneous materials is described. Contrarily to the reported approaches which rely on statistical analysis, the mechanical properties fields are analyzed herein relying on a topological description of the sample. The spatial convolution function is approached using Hertz contact theory, and the obtained convolution kernel is used to retrieve the mechanical properties of the different phases. This approach is exemplified on results obtained at very low contact force (and thus very high spatial resolution) on a composite material sample made of micrometer-sized fibers in a polymeric matrix.